Detecting ulterior motives from verbal cues in group deliberations - Dunbar, Norah E.; Burgoon, Judee K.; Chen, Xunyu; Wang, Xinran; Ge, Saiying; Huang, Qing; Nunamaker, Jay (Frontiers in Psychology, 2023)
Forensic interviewing entails practitioners interviewing suspects to secure valid information and elicit confessions. Such interviews are often conducted in police stations but may also occur in field settings such as border crossings, security checkpoints, bus terminals, and sports venues (Vrij, 2014). Because these real-world interviews often lack experimental control and ground truth, this investigation explored whether results of non-forensic interviews generalize to forensic ones. Organizational espionage was simulated to determine 1) what verbal signals distinguish truth from deception, 2) whether deception in groups aligns with deception in dyads, and 3) whether non-forensic venues can be generalized to forensic ones. Engaging in a mock hiring deliberation, participants (4-5 strangers) reviewed and discussed resumes of potential candidates. Surreptitiously, two group members assigned the role of “organizational spies” attempted to persuade the group to hire an inferior candidate. Each group member presented notes from an interview of “their” candidate, followed by a discussion of all candidates. Spies were to use any means possible, including deception, to persuade others to select their candidate. A financial incentive was offered for having one’s candidate chosen. The interview reports and discussion were transcribed and analyzed with SPLICE. Deceivers were perceived as less trustworthy than truthtellers, especially when the naïve players won but overall, deceivers were difficult for non-spies to detect even though they were seen as less trustworthy than the naïve participants. Deceivers’ language was more complex and exhibited an “echoing” strategy of repeating others’ opinions. This collusion evolved naturally, without preplanning. No other verbal differences were evident, which suggests that the difference between spies and non-spies was subtle and difficult for truth-tellers to spot.